South Korea to Create the 'Second Venture Boom': From Startups to Unicorn Companies - Jung Hun Lee; Tae Yeong Kim; Kyung-Min Jang; Jeong Ho Jeon; Young Bae Kim; Byeong Chul Jeong; Sang Hee Lee (Tehran University of Medical Sciences, 2022)
Not applicable.